Pengaruh Prosocial dan Intrinsic Motivation terhadap Employee Engagement dengan Mediasi Affective Commitment di Rumah Sakit Gigi dan Mulut - Juslily, Marta; Turnip, Dedianto; Gunawan, Andreas Wahyu (Universitas Proklamasi 45, 2025)
Employee engagement has become a topic of research and discussion among practitioners and academics in recent years. Many healthcare workers are experiencing job dissatisfaction, stress, and burnout. Many feel unappreciated by their organizations and are considering quitting due to long working hours. This situation leads many healthcare professionals to contemplate leaving their jobs. This research contributes to filling the gap in studies on educational dental teaching hospitals (RSGM) industries regarding the influence of prosocial and intrinsic motivation on employee engagement, mediated by affective commitment. The hypothesis was tested on samples from 224 healthcare and medical personnel at 5 Educational RSGM, using structural equation modeling (SEM) with AMOS software version 24. The test results indicated that prosocial motivation had no significant impact on employee engagement, whereas the other six hypotheses were confirmed as significant.